2021
DOI: 10.1016/j.artd.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Eradicating Fungal Periprosthetic TKA “Super-infection”: Review of the Contemporary Literature and Consideration of Antibiotic-Impregnated Dissolving Calcium Sulfate Beads as a Novel PJI Treatment Adjunct

Abstract: Fungal periprosthetic joint infections are an uncommon but potentially devastating complication of arthroplasty surgery. The concurrent presence of a coexistent bacterial pathogen—a so called “super-infection”—adds further complexity. With delays to definitive diagnosis and a large number of procedures before cure, the associated physical and psychological morbidity is considerable. Beyond this, the economic and resource burden can be substantial. This case report presents the successful rapid treatment of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A total of 63 studies on fungal PJI were found. A total of 372 fungal PJI cases were retrieved, most of which were collected from case reports [ 12 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], small case series [ 15 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 63 studies on fungal PJI were found. A total of 372 fungal PJI cases were retrieved, most of which were collected from case reports [ 12 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], small case series [ 15 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ...…”
Section: Resultsmentioning
confidence: 99%
“…The non-exothermic setting of CaSO 4 allows for almost all antimicrobial agents to be utilized (McPherson et al, 2021;Laycock et al, 2018). In PJI treatment, antibiotic-loaded CaSO 4 (ALCS) has been utilized since the late 1990s and ALCS application continues to evolve (Andreacchio et al, 2019;Kenna et al, 2018;Kurmis, 2021;Luo et al, 2016;Morley et al, 2022;Trujillo et al, 2017;Zhang et al, 2020;Ferguson et al, 2014;Abosala and Ali, 2020).…”
Section: Introductionmentioning
confidence: 99%